Analisis Implementasi Rencana Pelaksanaan Pembelajaran di MTs Madinatussalam - Dahlyanarpila, Suci; Fadlan, Izhar; Siregar, Ryan Mulana; Amanda, Ahmad (Global Education Journal, 2025)
This study aims to analyze the implementation of the Lesson Implementation Plan (RPP) at Madrasah Tsanawiyah (MTS) Madinatussalam. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The main focus of this study is to describe the process of preparing, implementing, and evaluating the RPP and identifying factors that influence the success of its implementation. The results of the study indicate that although the RPP prepared by teachers is in accordance with the established curriculum, there are several important components that are still lacking. In addition, the implementation of learning at MTS Madinatussalam shows varying levels of effectiveness, with some meetings achieving good success criteria, while others still need improvement. Factors such as lack of learning resources, student motivation, and support from the school are challenges in implementing the RPP.  Overall, this study concludes that the success of the learning process is greatly influenced by the quality of RPP planning and implementation. Therefore, increasing training for teachers and providing adequate learning resources is needed to achieve optimal learning outcomes.